2011
DOI: 10.1152/ajpendo.00514.2010
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin and its receptors contribute in a tissue-specific manner to the sex-dependent metabolic (fed/fasting) control of growth hormone axis in mice

Abstract: Córdoba-Chacón J, Gahete MD, Castaño JP, Kineman RD, Luque RM. Somatostatin and its receptors contribute in a tissuespecific manner to the sex-dependent metabolic (fed/fasting) control of growth hormone axis in mice. Am J Physiol Endocrinol Metab 300: E46 -E54, 2011. First published October 13, 2010; doi:10.1152/ajpendo.00514.2010.-Somatostatin (SST) inhibits growth hormone (GH) secretion and regulates multiple processes by signaling through its receptors sst1-5. Differential expression of SST/ssts may contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 74 publications
(126 reference statements)
4
21
0
Order By: Relevance
“…In particular, the hypothalamic-pituitary-adrenal axis hyperactivity has been found in chronic diseases affecting the endocrine, cardiovascular and nervous systems among the aging population [28]. Furthermore, somatostatin exerts pleiotropic effects through a family of 5 G protein-coupled receptor subtypes with 7 transmembrane domains, termed sst1-5, which are encoded by separate genes expressed throughout the body, including the brain, pituitary and gastrointestinal tract, where the relative abundance of receptor subtypes as well as of somatostatin is also dependent on the species, tissue, gender, and nutritional state analyzed [29]. Beyond changes in somatostatin output, also receptorial sensitivity might contribute critically to the dysfunctional modulation of neurotransmission, metabolism, and immune function, as well as the inhibition of endocrine and exocrine secretion possibly involved in pathophysiology of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the hypothalamic-pituitary-adrenal axis hyperactivity has been found in chronic diseases affecting the endocrine, cardiovascular and nervous systems among the aging population [28]. Furthermore, somatostatin exerts pleiotropic effects through a family of 5 G protein-coupled receptor subtypes with 7 transmembrane domains, termed sst1-5, which are encoded by separate genes expressed throughout the body, including the brain, pituitary and gastrointestinal tract, where the relative abundance of receptor subtypes as well as of somatostatin is also dependent on the species, tissue, gender, and nutritional state analyzed [29]. Beyond changes in somatostatin output, also receptorial sensitivity might contribute critically to the dysfunctional modulation of neurotransmission, metabolism, and immune function, as well as the inhibition of endocrine and exocrine secretion possibly involved in pathophysiology of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Intact and hypophysectomized adult male and female CD1 mice (8 to 12 weeks old) were purchased from Charles River Laboratories (Wilmington, MA). Livers from male and female wild-type and somatostatin-deficient mice (9 to 12 week old) were provided by R. M. Luque and R. D. Kineman (University of Illinois at Chicago, Chicago, IL) and were described previously (70,71). Liver tissues were collected from 8-to 12-week-old male and female hepatocyte-specific STAT5a/STAT5b-knockout (KO) mice and corresponding floxed control mice, provided by L. Hennighausen (NIDDK, NIH, Bethesda, MD) (72).…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction, quantification, and reverse transcription as well as the development, validation, and application of qPCR to measure the expression levels of different mouse transcripts have been previously reported elsewhere by our group (7,8). Total RNA was extracted from hypothalamus, pituitary gland, liver, and pancreas using an Absolutely RNA miniprep kit, with deoxyribonuclease treatment, following the manufacturer's protocol (Stratagene).…”
Section: Rna Extraction Reverse Transcription and Quantitative Realmentioning
confidence: 99%
“…The expression level of this housekeeping gene did not differ between groups in any of the tissues analyzed. Specific sets of primer sequences used in this study have been previously reported (7,8,10,15,16), except for epithelial growth factor receptor (egf-r; accession number NM_207655.2; sense: ACAAGTAACAGGCTCAC-CCAACT, and antisense: GCAGGTTCTCCAAAGGGATT; product size: 214 bp). It should be noted that, as previously reported (13,14) and based on the stringent criteria to maximize specificity and efficiency, the qPCR technique, as applied, can be used to accurately quantify copy numbers for all mouse transcripts included in this study.…”
Section: Rna Extraction Reverse Transcription and Quantitative Realmentioning
confidence: 99%